An Improved, Fully Heterogeneous, Diastereoselective Synthesis of (Z)-α-Bromonitroalkenes - Palmieri, Alessandro; Gabrielli, Serena; Ballini, Roberto (Synlett, 2013)
α-Bromonitroalkenes are both key starting materials for the preparation of complex structures and possess antimicrobial activity. In this context, we disclose a simple, fully heterogeneous synthetic approach for their preparation in good overall yields.
Keywords: Henry reaction; dehydration; diastereoselectivity; α-bromonitroalkanes; heterogeneous catalysis